Pendidikan Jurnalisme Warga (Citizen Journalism) pada Siswa di SMA Muhammadiyah 2 Kalampangan, Palangka Raya: Citizen Journalism Education for Students at Muhammadiyah 2 High School Kalampangan, Palangka Raya - Rosmilawati, Srie; Handayani, Indah Tri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Citizen journalism or citizen journalism can now be done by anyone, anywhere, without special knowledge in delivering the news. This can be a severe problem because some citizen journalists only deliver news that occurs around the real world without fulfilling the news elements, namely 5W + 1H, and do not understand the journalistic code of ethics. So that the news delivered can violate the rules in journalism. Citizen journalism education action is needed to solve problems in most people in Indonesia, especially among students of SMA Muhammadiyah 2 Kalampangan, Palangkaraya. For this reason, all students must be able to participate in making social media a means of journalism by using journalism principles such as writing procedures and journalistic code of ethics. This citizen journalism education program, is a program in educating high school students using social media to become professional citizen journalists and can be used as a reference for the community in Kalampangan in obtaining information around their environment. It is hoped that in the future, the students of SMA Muhammadiyah 2 Palangkaraya can apply citizen journalism education into their daily life and be able to transmit it to the community around Kalampangan village.